2017
DOI: 10.4236/ojoph.2017.74035
|View full text |Cite
|
Sign up to set email alerts
|

Non-Penetrating Femtosecond Laser Intrastromal Astigmatic Keratotomy Performed during Laser-Assisted Cataract Surgery: Results on Keratometric Astigmatism

Abstract: Purpose: To investigate the efficacy of non-penetrating femtosecond laser intrastromal astigmatic keratotomy (ISAK) in terms of topographic and refractive changes. Methods: Retrospective study including 42 eyes (35 patients) with a corneal astigmatism between 0.5 and 1.5 D. All eyes underwent femtosecond laser-assisted cataract surgery with ISAK for astigmatism management using the Catalys laser system (Johnson & Johnson Vision). Visual acuity, refraction, as well as corneal topographic and corneal endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The aim of this retrospective study was to evaluate the efficacy of intrastromal arcuate incisions with a femtosecond laser using a calculated customised approximation curve based on corneal biomechanics. Several studies have already reported that the femtosecond laser is a safe, reliable method with well-reproducible arcuate intracorneal incisions for the correction of astigmatism, but we hypothesised that customised preoperative biomechanical modelling can further improve the surgical outcome [ 9 , 10 ]. Further prospective studies with a control group need to be performed in order to better assess the potential of the method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this retrospective study was to evaluate the efficacy of intrastromal arcuate incisions with a femtosecond laser using a calculated customised approximation curve based on corneal biomechanics. Several studies have already reported that the femtosecond laser is a safe, reliable method with well-reproducible arcuate intracorneal incisions for the correction of astigmatism, but we hypothesised that customised preoperative biomechanical modelling can further improve the surgical outcome [ 9 , 10 ]. Further prospective studies with a control group need to be performed in order to better assess the potential of the method.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that femtosecond laser-assisted astigmatic keratotomy is a good and effective method for reducing corneal and, therefore, refractive astigmatism in cataract surgery [ 9 , 10 ]. This astigmatic correction was found to have a good safety profile with very good refractive topographic stability over time without a significant change in endothelial cell density [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%